The Adaptation of Academic Motivation Scale to Turkish - (:unkn) unknown (EDAM, 2012)
The current study evaluated the psychometric evidence of Turkish form of the Academic Motivation Scale. The scale was based on the tenets of self-determination theory. It was designed to assess an individual's academic motivation if intrinsically or extrinsically driven with 28 questions. University form of the scale was translated into Turkish through appropriate methodological procedures. 390 university students completed the forms. Outcome variables also included the measures of test anxiety and communal mastery. Hypotheses testing and exploratory factor analyses methods were used. Confirmatory factor analyses confirmed the seven-factor structure. Cronbach's alpha and item-total correlation coefficients were also calculated. The Turkish version of the scale has satisfactory levels of validity and reliability. Reanalyzing the measurement properties of the scale is recommended.
Keywords: Academic Motivation Scale; Adaptation; Reliability; Validity; SELF-DETERMINATION; ACHIEVEMENT GOALS; FIT INDEXES; CONSTRUCTION; VALIDITY; AMOTIVATION; COMPETENCE; EDUCATION; MASTERY; WELL